Grounded christianity – modern relation between Church and world - Wróblewska, Anna (Studia Teologiczne Białystok Drohiczyn Łomża, 2022)
This very text describes title “grounding Christianity” as one of the reasons of its actual crisis. The author touches on this subject matter especially from the perspective of the latest doctrinal and ministral interests. Illustrative issues are: ecology, teaching about resurrection and (in a broad sense) personalism.